Race and ethnicity in America - Iceland, John, 1970- (Sociology in the 21st century (University of California Press) ;, 2017)
Race and Ethnicity in America examines patterns and trends in racial and ethnic inequality over recent decades. John Iceland shows how color lines have generally softened over time in the United States but deep-seated inequalities remain-generally, blacks, American Indians, and some Hispanics fare less well than others. Among these groups, the underlying causes of the disadvantages vary, ranging from the legacy of racism, current discrimination, differences of human capital, the unfolding process of immigrant incorporation, and cultural responses to structural conditions. Throughout the book,